Microbial community and genetic homology of Anaplasma harbored by Haemaphysalis tibetensis collected in Yadong county, Tibet Autonomous Region - Shiwei SUN; Duojiouzhu; Ruishan LI; Wenkai ZHANG; Zhen HE; Zhenhua LU; Zhongjun SHAO (Editorial Office of Chinese Journal of Public Health, 2023)
ObjectiveTo genetically characterize microbial community and Anaplasma - a major pathogen harbored by Haemaphysalis tibetensis collected in Yadong county, Tibet Autonomous Region. MethodsTotally 141 ticks parasitizing on yaks were collected in Yadong county in May 2022 and the species of the ticks were identified according to amplified sequences of mitochondrial 16s rDNA of Ixodes. High-throughput sequencing was carried on the identified Haemaphysalis tibetensis using the Illumina Novaseq 6000 platform. The resulting raw data underwent processing for assembly, gene prediction, abundance analysis, and taxonomic prediction. The 16S rDNA gene fragment of Anaplasma was amplified and sequenced with nested PCR for phylogenetic analysis. ResultsOut of 141 adult tick samples collected, 121 were positively identified as Haemaphysalis tibetensis. According to species annotation with the National Center for Biotechnology Information (NCBI)-NR database, the most prevalent microorganisms were eukaryotes (19.78%) and bacteria (13.54%), with the dominant genera of Anaplasma, Trypanosoma, Psychrobacter, and Rickettsia and the dominant species of phagocytophilum group, Trypanosoma theileri, and spotted fever group rickettsia. Among the bacterial florae, the dominant phyla were Proteobacteria, Bacteroidetes, and Firmicutes. The phylogenetic analysis revealed a high homology of the tick-born Anaplasma and Anaplasma ovis. ConclusionIn the research area, the dominant tick species parasitizing on yaks in this region is the Haemaphysalis tibetensis and the major genotype of the tick-born Anaplasma is Anaplasma ovis. The results suggest that local residents and livestock could be exposed to various tick-borne pathogens and targeted surveillance and preventive measures against tick-borne diseases should be enhanced.